Geopolitics: The Seen and Unseen in Small State Foreign Policy - Sulg, Mari-Liis; Crandall, Matthew (Journal of Regional Security, 2020)
Geopolitics, a combination of geography and politics by default resembles the power politics of large states. As small states have little resources to pursue power-based foreign policy, one can wonder if the geopolitics of small states matter. This paper argues that small states use geopolitical tools to locate themselves on the winners’ side. The current paper takes a closer look into the post-Cold War foreign policies of Estonia and Finland that originate from opposite principles. Estonia’s principle of „never alone again“, locates itself in the West. This differs from its neighbour Finland’s principle „always alone“, which locates itself as a strategic regional actor. To highlight the same but somewhat different reasoning in their foreign policies, the annexation of Crimea and the war in Ukraine are studied in this article by applying critical geopolitics as a methodological tool.